Thermoelectric Enhancements in PbTe Alloys Due to Dislocation‐Induced Strains and Converged Bands. Issue 12 (15th May 2020) - Wu, Yixuan; Nan, Pengfei; Chen, Zhiwei; Zeng, Zezhu; Liu, Ruiheng; Dong, Hongliang; Xie, Li; Xiao, Youwei; Chen, Zhiqiang; Gu, Hongkai; Li, Wen; Chen, Yue; et al.
Abstract: In‐grain dislocation‐induced lattice strain fluctuations are recently revealed as an effective avenue for minimizing the lattice thermal conductivity. This effect could be integratable with electronic enhancements such as by band convergence, for a great advancement in thermoelectric performance. This motivates the current work to focus on the thermoelectric enhancements of p‐type PbTe alloys, where monotelluride‐alloying and Na‐doping are used for a simultaneous manipulation on both dislocation and band structures. As confirmed by synchrotron X‐ray diffractions and Raman measurements, the resultant dense in‐grain dislocations induce lattice strain fluctuations for broadening the phonon dispersion, leading to an exceptionally low lattice thermal conductivity of ≈0. 4 W m‐K −1 . Band structure calculations reveal the convergence of valence bands due to monotelluride‐alloying. Eventually, the integration of both electronic and thermal improvements lead to a realization of an extraordinary figure of merit zT of ≈2.5 in Na0.03 Eu0.03 Cd0.03 Pb0.91 Te alloy at 850 K. Abstract : Simultaneous manipulation of in‐grain dislocations for lattice thermal conductivity reduction and band convergence for electronic enhancement leads to a realization of an extraordinary thermoelectric figure of merit in p‐PbTe alloys.